2014
DOI: 10.1016/j.schres.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch and lexical retrieval gestures are associated with visual information processing, verbal production, and symptomatology in youth at high risk for psychosis

Abstract: Introduction Gesture is integrally linked with language and cognitive systems, and recent years have seen a growing attention to these movements in patients with schizophrenia. To date, however, there have been no investigations of gesture in youth at ultra high risk (UHR) for psychosis. Examining gesture in UHR individuals may help to elucidate other widely recognized communicative and cognitive deficits in this population and yield new clues for treatment development. Method In this study, mismatch (indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Finally, our analyses were restricted to gray matter volume in healthy individuals, and were limited to only gesture production. However, both we and others have recently demonstrated that gestures differ in important clinical populations (e.g., psychosis and psychosis risk) [Millman et al, 2014;Straube et al, 2013Straube et al, , 2014 although this work has not included beat gestures. Investigating beat gestures in patient populations with respect to brain volumes in the future may be informative for our understanding of both the disease processes and co-speech gestures, particularly in psychosis populations given their known cerebellar motor deficits Mittal, 2014, 2015;Dean et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our analyses were restricted to gray matter volume in healthy individuals, and were limited to only gesture production. However, both we and others have recently demonstrated that gestures differ in important clinical populations (e.g., psychosis and psychosis risk) [Millman et al, 2014;Straube et al, 2013Straube et al, , 2014 although this work has not included beat gestures. Investigating beat gestures in patient populations with respect to brain volumes in the future may be informative for our understanding of both the disease processes and co-speech gestures, particularly in psychosis populations given their known cerebellar motor deficits Mittal, 2014, 2015;Dean et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, volumetric investigations of the cerebellum in a subset of these participants were undertaken as part of a control group in a clinical investigation with respect to motor learning [Dean et al, ], and a lifespan developmental investigation focusing on cognition [Bernard et al, ]. These participants also served as controls in a comparison of gesture‐language mismatch between healthy individuals and a clinical group [Millman et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, two reports of spontaneous gesture use suggest alterations in gesture use in unmedicated schizotypal adolescents and youth at ultrahigh risk for psychosis [28,29]. The authors investigated the spontaneous frequency of well-defined gesture categories, such as iconic, metaphoric, beat and deictic (pointing) gestures, during a natural interview situation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors investigated the spontaneous frequency of well-defined gesture categories, such as iconic, metaphoric, beat and deictic (pointing) gestures, during a natural interview situation. Besides the quantitative reduction in spontaneous gesture use [29], subjects at risk also demonstrated qualitative alterations in gesture content [28]. In fact, increased mismatch errors (incongruence between content of speech and gesture) and more retrieval gestures (gestures during speech pause while the participant is searching an expression) were reported in subjects at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation